The Lost Knowledge of Christ : Contemporary Spiritualities, Christian Cosmology, and the Arts - White, Dominic (Book collections on Project MUSE., 2015)
Did Christianity once teach secret knowledge? Dominic White argues that the early Church in fact taught a wonderful wisdom about the cosmos. Christian cosmology offers resources for addressing many of the problems, questions, and issues that are faced both in the church and in society. It does not provide instant answers; rather, it is in some ways more like the parables of Jesus, stories that challenge our view of the world and invite reflection and contemplation. This 'lost knowledge' sheds new light on many biblical teachings and areas of controversy within Christianity: the meaning of repentance; the mystery of the cross; Jesus' ascent through the heavens; angels and stars; the body and the feminine; justice and ecology; and liturgy, art, music, and dance. The Lost Knowledge of Christ shares the cosmic, psychological, and artistic focus of today's nonreligious spiritualities and offers some surprising responses. Images, music, and videos that correspond with the chapters can be found at lostknowledgeofchrist.wordpress.com.